Complex clinical case with Class III and open bite: stability after seven years - Rhita Cristina Cunha Almeida; Livia Kelly Ferraz Nunes; Ingrid Balbino Sousa Coelho Vieira; Felipe de Assis Ribeiro Carvalho; Marco Antonio de Oliveira Almeida
ABSTRACT A healthy 15-year-old boy with anterior open bite, edge-to-edge transverse discrepancy, and Class III skeletal relationship sought a nonsurgical orthodontic treatment. The patient was treated with premolars extraction, a Hyrax expander and intrusion mechanics with vertical elastics. This mechanics allowed for excellent facial and occlusal results. The final occlusion presented Class I molar and canine relationships, ideal overjet and overbite, and straight facial profile. Analysis of the posttreatment and follow-up radiographs showed that the treatment outcomes remained stable seven years after active orthodontic treatment. Thus, although combined orthodontic and surgical treatment should be considered for patients with this skeletal malocclusion, this case report proves that well controlled orthodontic movement with the patient's cooperation can be a valid alternative treatment, with good and stable outcomes for patients who refuse surgery.